2018
DOI: 10.1080/21691401.2018.1511572
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological effects of nanoencapsulation of human-based dosing of probucol on ratio of secondary to primary bile acids in gut, during induction and progression of type 1 diabetes

Abstract: Introduction: The ratio of secondary to primary bile acids changes during Type 1 Diabetes (T1D) development and these effects might be ameliorated by using cholesterol lowering drugs or hydrophilic bile acids. Probucol is a cholesterol-lowering drug, while ursodeoxycholic acid is a hydrophilic bile acid. This study investigated whether nanoencapsulated probucol with ursodeoxycholic acid altered bile acid ratios and the development of diabetes. Methods: Balb/c mice were divided into three groups and gavaged dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…Of the endogenous bile acids, the tertiary bile acid ursodeoxycholic acid (UDCA) has been shown to be the most potent anti-inflammatory and anti-apoptotic bile acid with significant cell protective properties with its mechanism of action being correlated with its cellular uptake by muscle and β-cells [15][16][17][18][19][20] . Tsuchida, T., et al; have shown that chronic oral administrations of UDCA in insulin resistant animals have been associated with cardio-metabolic improvement as a result of its cellular uptake 21 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Of the endogenous bile acids, the tertiary bile acid ursodeoxycholic acid (UDCA) has been shown to be the most potent anti-inflammatory and anti-apoptotic bile acid with significant cell protective properties with its mechanism of action being correlated with its cellular uptake by muscle and β-cells [15][16][17][18][19][20] . Tsuchida, T., et al; have shown that chronic oral administrations of UDCA in insulin resistant animals have been associated with cardio-metabolic improvement as a result of its cellular uptake 21 .…”
mentioning
confidence: 99%
“…The flow rate set at 0.25 mL/min and the mobile phase was methanol (65%) and water (35%) at pH 2.9, with the standards and quality control samples being within the range of 1-1000 ng/ml. The analysed bile acids CDCA, LCA and UDCA had retention times of 2.6, 5.1 and 1.5 minutes respectively, with a flow rate of 1.5 L/min using our well-established methods 18,42,72,73 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At hyperglycemic state (35.5 mM glucose), the three control groups (F1, F3 and F5) showed similar cell viability, and oxidative stress levels, and incorporation of ursodeoxycholic acid enhanced cell viability among all microcapsules, but reduced oxidative stress only in the NM30D group (F2). Some of our previous studies [45][46][47] suggest that UDCA in microcapsule formulation may exert a protective effect on pancreatic β-cells, desirable insulin production, and cell functionality and reduced inflammatory profile suggesting potential applications in diabetes. The positive effects of NM30D-ursodeoxycholic acid on cell viability and oxidative stress (Figure 4) may be associated with the positive effects observed on the electrokinetic voltage and Zeta-potential (Figure 1), and strong targetedrelease effects observed on microcapsules' release of probucol ( Figure 2C) as well as the significant increase in probucol cellular-uptake observed (Figure 3).…”
Section: Cellular Viability and Oxidative Stress Activitiesmentioning
confidence: 99%
“…The addition of DCA to gliclazide promoted the transport of gliclazide across the blood–brain barrier to a factor of three in healthy rats and a factor of four in diabetic rats [ 159 ]. Several studies have shown that the addition of DCA to drug carriers improves the mechanical and osmotic stability of drug carriers, improved controlled release delivery outcomes, and chemical stability with probucol addition [ 93 , 130 , 132 , 136 , 148 , 154 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 ]…”
Section: Bile Acidsmentioning
confidence: 99%